PENGARUH TRANSPARANSI ANGGARAN TERHADAP PARTISIPASI MASYARAKAT DALAM PENGAWASAN KEUANGAN NEGARA - Indrawan Saputra, M. Rizky; Kurnia Sobana Putra, Adrian; Ahyar, Syahriful; Saputra, Bagas (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
This study aims to analyze the relationship between budget transparency and public participation in state financial supervision in Tanjungpinang City. The research method used is quantitative descriptive, with data collection techniques through observation, interviews, and documentation studies. The results of the study indicate that the level of budget transparency in Tanjungpinang City has increased through the implementation of digital systems and openness of public information, although there are still challenges related to public financial literacy and the use of budget information. In addition, there is a significant relationship between budget transparency and public participation in state financial supervision. The more transparent the budget information provided by the government, the greater the public participation in supervision. Factors that influence public participation include public expectations and desires, self-awareness, and government support, while the main obstacles come from employment and economic factors, as well as low levels of public education. This study provides recommendations for the government to continue to improve budget transparency and overcome obstacles to public participation in order to achieve better and more accountable governance.